The The Effect of Ultrasonic activation on the Microstructure and Phase Transformation of Porous Ni-Ti Shape Memory Alloys - Maashaa, Dovchinvanchig; Narmandakh, Baasanjargal (Scientific transaction of the National University of Mongolia. Physics, 2024)
Porous Ni-Ti shape memory alloys (SMAs) have been widely studied in Biomaterial for biomedical applications because they have a porous structure similar to human bone and corrosion resistance. A porous Ni-Ti SMAs was obtained by self-propagating high-temperature synthesis (SHS) and investigated its microstructure and phase transformation. This article presents the results of a study of changes in the microstructure and phase transformation of porous Ni-Ti SMAs when Ni and Ti metal powders were preliminarily subjected to ultrasonic activation at different amplitude (5-25μm). The results show that the microstructure of porous Ni-Ti SMAs consists of Ni-Ti matrix and Ni-Ti2 precipitates. Two-step phase transformation was observed in porous Ni-Ti alloys.